Implementasi Algoritma Boyer Moore Pada Kamus Perbedaan Kata Dalam Bahasa Inggris British dan Bahasa Inggris America - Sindi Sekar Sari; Garuda Ginting (Journal of Informatics Management and Information Technology, 2021)
British English and American English are the smallest cultural products of development in English, which is known for its variants of English. British English and American English differ in pronunciation, spelling and vocabulary. For that we need an application that contains word differences in British English and American English. Where people and students can learn and understand the differences between the two languages. The difference application between British English and American English is used by all people and students by searching from an existing application in the application that has been made. And it can be understood if the public and students succeed in finding the differences between the two languages ??which have been determined according to the existing pattern, the right search for solutions in the application. Search for differences in British English and American English words is designed using the Stringmatching Method. Application development uses the UML design method and is built on the Android platform.